Anterior Surgical Treatment of Cervical Spondylotic Myelopathy: Review Article. Issue 1 (February 2015) - Quinn, John C.; Kiely, Paul D.; Lebl, Darren R.; Hughes, Alexander P.
Background: Cervical spondylotic myelopathy (CSM) is a common indication for cervical spine surgery. Surgical options include anterior, posterior, or combined procedures each with specific advantages and disadvantages. Questions/Purposes: This article will provide a description of the various anterior alternatives and discuss the available evidence used in guiding the surgical decision making process with the aim of answering the following questions: (1) What anatomical/disease related factors favor anterior over posterior surgeries? (2) What are the common anterior procedures and how safe and effective are they? (3) What are the most effective options for multilevel CSM? (4) Is there a role for motion preservation? An additional objective is to discuss technical advances that have improved success rates for anterior procedures. Methods: The PubMed database was searched. Keywords were CSM and anterior surgery. Three hundred eighty two articles were found one hundred three were reviewed. Articles describing anterior cervical techniques were selected along with studies describing the various anterior techniques or comparisons of anterior to posterior techniques. Results: Anterior decompression and fusion procedures are more effective than posterior procedures for patients with primarily ventrally located compression especially in the presence of cervical kyphosis. ACDF, ACCF, and hybrid combinations are safe and effective treatment options for multilevel CSM. Anterior procedures may be more cost effective and result in significantly improved postoperative quality of life and health-related quality of life measures compared to posterior procedures. Conclusion: Anterior cervical decompression techniques are safe and effective in the treatment of CSM. Anterior surgeries may be preferable to posterior approaches, when considering health-related quality of life measures and cost effectiveness.